Improved early development of porcine cloned embryos by treatment with quisinostat, a potent histone deacetylase inhibitor - Anukul TAWEECHAIPAISANKUL; Jun-Xue JIN; Sanghoon LEE; Geon A KIM; Yoon Ho SUH; Min Seok AHN; Se Jun PARK; Byeong You LEE; Byeong Chun LEE (The Journal of Reproduction and Development, 2018)
Recently, the modification of the epigenetic status of somatic cell nuclear transfer (SCNT) embryos by treatment with histone deacetylase inhibitors (HDACis) has made it possible to alter epigenetic traits and improve the developmental competence of these embryos. In the current study, we examined the effects of an HDACi, quisinostat (JNJ), on the in vitro development of porcine cloned embryos and their epigenetic nuclear reprogramming status. SCNT embryos were cultured under various conditions, and we found that treatment with 100 nM JNJ for 24 h post activation could improve blastocyst formation rates compared to the control (P < 0.05). Therefore, this was chosen as the optimal condition and used for further investigations. To explore the effects of JNJ on the nuclear reprogramming of early stage embryos and how it improved cloning efficiency, immunofluorescence staining and quantitative real-time PCR were performed. From the pseudo-pronuclear to 2-cell stages, the levels of acetylation of histone 3 at lysine 9 (AcH3K9) and acetylation of histone 4 at lysine 12 (AcH4K12) increased, and global DNA methylation levels revealed by anti-5-methylcytosine (5-mC) antibody staining were decreased in the JNJ-treated group compared to the control (P < 0.05). However, JNJ treatment failed to alter AcH3K9, AcH4K12, or 5-mC levels at the 4-cell embryo stage. Moreover, JNJ treatment significantly upregulated the expression of the development-related genes OCT4, SOX2, and NANOG, and reduced the expression of genes related to DNA methylation (DNMT1, DNMT3a, and DNMT3b) and histone acetylation (HDAC1, HDAC2, and HDAC3). Together, these results suggest that treatment of SCNT embryos with JNJ could promote their developmental competence by altering epigenetic nuclear reprogramming events.